Medical uses for silver nitrate in the urinary tract (Review). (2022) - Sekito, Takanori; Sadahira, Takuya; Watanabe, Toyohiko; Maruyama, Yuki; Watanabe, Tomofumi; Iwata, Takehiro; Wada, Koichiro; Edamura, Kohei; Araki, Motoo; Watanabe, Masami
No abstract available